Towards a national network of community seedbanks in South Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Through capacity development and action research support to South Africa's National Plant Genetic Resources Centre (NPGR, under the Department of Agriculture, Forestry and Fisheries) and district level extension officials, the first three community seedbanks of an envisioned national network were established in marginalized smallholder farming areas.